Analisis Hubungan Tingkat Aktivitas Fisik dan Status Gizi Pada Remaja di Lembaga Pembinaan Khusus Anak (LPKA) Bandung - Ahdan Abdillah Ad-Dauli; Ramani, Nia Sri; Bahri, Samsul; Khoerunnisa, Dinda (Institut Teknologi Bandung, 2024)
This study aims to analyze the relationship between the level of physical activity and nutritional status in children fostered by the Lembaga Pembinaan Khusus Anak (LPKA). The research method used in this study is descriptive quantitative research with an observational study research design. The population used was 140 adolescents fostered by LPKA Bandung. The sampling technique used in this study used purposive sampling. So that the subjects used were 40 people. The instrument used to determine the level of physical activity is using the Baecke Physical Activity Questionnaire (BPAQ) and measuring nutritional status using the Body Mass Index (BMI). The findings in this study were that most of the research subjects had a moderate level of activity (52.5%) with normal / thin nutritional status (72.5%) while the rest had a mild level of physical activity (47.5%) with excess nutritional status (27.5%). In addition, there is a significant relationship between the level of physical activity with nutritional status with (pvalue 0.049) The conclusion of this study is that adolescents who have moderate physical activity levels mostly have normal / less nutritional status, while adolescents who have mild physical activity levels mostly have more nutritional status. In addition, there is a significant relationship between the level of physical activity and nutritional status in adolescents in LPKA Bandung.